USM, HEHD SIGNS MOU FOR ACADEMIC AND RESEARCH COLLABORATION - MPRC, Pusat Media & Perhubungan Awam (USM, 2016)
USM, PENANG, 7 November 2016 Universiti Sains Malaysia (USM) today signed a Memorandum of Understanding (MoU) with Hadhramout Establishment for Human Development (HEHD) Yemen to strengthen, promote and develop a longterm academic collaboration in undergraduate and postgraduate education and research cooperation between both parties.